2015
DOI: 10.2500/aap.2015.36.3879
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micronized cellulose powder on the efficacy of topical oxymetazoline in allergic rhinitis

Abstract: clinicaltrials.gov identifier: NCT01986582.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…However, several previous studies have evaluated the efficacy of NCP in patients who have stopped the use of intranasal steroids or have never used them before and during the enrollment,8911 which is similar to our study. A recent study has demonstrated the efficacy of NCP in enhancing oxymetazoline-increased PNIF in adults with moderate to severe persistent perineal AR 24. A real-life study on the effects of NCP as an add-on to intranasal as-needed treatment, in subjects with pollen AR has demonstrated a decrease in combined symptom and medication scores (CSMS) in patients receiving NCP when compared to those receiving placebos 25.…”
Section: Discussionmentioning
confidence: 99%
“…However, several previous studies have evaluated the efficacy of NCP in patients who have stopped the use of intranasal steroids or have never used them before and during the enrollment,8911 which is similar to our study. A recent study has demonstrated the efficacy of NCP in enhancing oxymetazoline-increased PNIF in adults with moderate to severe persistent perineal AR 24. A real-life study on the effects of NCP as an add-on to intranasal as-needed treatment, in subjects with pollen AR has demonstrated a decrease in combined symptom and medication scores (CSMS) in patients receiving NCP when compared to those receiving placebos 25.…”
Section: Discussionmentioning
confidence: 99%
“…In another interesting clinical trial, hydroxypropylmethylcellulose (HPMC) was tested in the treatment of allergic rhinitis [ 137 ]. It has been hypothesized that inhaled allergens, as well as other substances, can disrupt the integrity of nasal mucosal lining thus favoring the contact of the body with external harmful agents.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…To down regulate inflammation and mucosal congestion, decongestant substances such as oxymetazoline nasal spray, 0.05% are often used. Recently, HPMC has been employed in addition to oxymetazoline [ 137 ] due to its known mucoprotective effects based on its viscoelastic properties. Forty allergic rhinitis patients were divided into two groups: the first was locally treated by oxymetazoline, followed by HPMC, the second was treated similarly but instead of HPMC, lactose powder (placebo) was administered.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Indeed, the extensive clinical experience gathered so far does not suggest deleterious effects of CP: no signs of impaired mucosa or of plugging of the ostia of the paranasal sinuses have been detected after months of usage. The formulation even appears to have some “healing” effect on its own [6]. What we have documented in a real-life randomized double-blind study in subjects with seasonal allergic rhinitis is a moderate slowdown of the nasal mucociliary clearance as assessed by saccharine test after 1 month of regular application [7].…”
mentioning
confidence: 99%